Dysplastic barrett's esophagus: Surveillance, treatment and follow-up – A systematic horizontal review - Valini, Stephanie Assunção; Chehter, Ethel Zimberg (Seven Editora, 2023)
INTRODUCTION: Gastroesophageal reflux disease (GERD) is important due to its recurrence, being the main reason for consultations and with prevalence higher than 25% in Asia and Southeast Europe. The most feared complication of GERD is esophageal adenocarcinoma (ECA), preceded by Barrett's esophagus (EB), defined as the replacement of the stratified squamous epithelium with an abnormal columnar epithelium with intestinal characteristics. The epidemiology still remains unknown due to the low specificity of the symptoms and the lack of consensus on the endoscopic characteristics for its diagnosis. In the dysplastic forms of EB with more chance of progression to ACE, there are few studies and better conducts in relation to dysplastic EB. OBJECTIVE: to clarify controversies about the conduct of dysplastic EB. METHOD:  horizontal review, PRISMA method through electronic search in PubMed, between 2018 and 2022, with descriptors: "Barrett's Esophagus" and "Surveillance AND dysplasia AND esophagus" for all age groups. Inclusion: articles in English, with compatible titles and abstracts. We obtained 620 results and after selection 17 articles were included. RESULTS: 13 articles indicate the Seattle Protocol for diagnosis and surveillance; 5, anti-reflux therapy before endoscopy and 12, confirmation of dysplasia by a specialized pathologist. Follow-up low-grade dysplasia (GBD): radiofrequency ablation therapy (ART) and surveillance are feasible in 13 articles, with ART preferred in 8 and surveillance in 4. High-grade dysplasia (DAG) follow-up: endoscopic therapies recommended in 12 articles. Follow-up after dysplastic eradication: periodic and continuous endoscopic surveillance indicated in 9 articles and treatment with proton pump inhibitors in 2 articles. DISCUSSION: Although the Seattle Protocol is recommended for surveillance, it covers a small part of the esophageal mucosa, besides being time-consuming and having low adherence. Controversies persist about the management of BPD, but, in general, ablation is recommended to the detriment of surveillance. There is consensus on endoscopic ablation therapy until complete eradication of DAG. Esophagectomy is not recommended. After eradication, continuous surveillance and proton pump inhibitors. CONCLUSION: Disagreements persist due to discrepancies between studies, especially in low-grade dysplastic EB. DOI:https://doi.org/10.56238/globalhealthprespesc-020